Transitional Identity as a Facilitator of Organizational Identity Change during a Merger - Clark, Shawn M.; Gioia, Dennis A.; Ketchen, David J.; Thomas, James B. (Administrative Science Quarterly, 2010)
We adopted an interpretive, grounded theory approach to study the processes by which organizational identities changed during the initial phases of a merger between two formerly rival healthcare organizations. Our investigation of two top management teams attempting to instigate this major change effort and lead their organizations toward completion of the merger revealed that the emergence of a transitional identity—an interim sense held by members about what their organizations were becoming—was critical to moving the change process forward. The transitional identity allowed executives in the two organizations to suspend their preexisting organizational identities and work toward creating a shared, new identity. The transitional identity appears to have been effective because it was ambiguous enough to allow multiple interpretations of what the merged organization would become to eventually coalesce into a common understanding, but not so ambiguous as to be threateningly unfamiliar. Overall, we present a process model of organizational identity change during a major change event that spanned two organizations, with the concept of transitional identity as its centerpiece.